Expression profile of the PIWI mRNAs protein family in human cells experimentally infected with Dengue Virus 4 (Research, Society and Development, 2021)
Objective: Evaluate the messenger RNAs (mRNA) PIWI proteins expression during infection with VDEN 4 in human hepatocyte cells. Materials and Methods: VDEN4 strain H778494 (JQ513335) was used, which was stored in Aedes albopictus cell culture (Clone C6 / 36) at the Arbovirology and Hemorrhagic Fevers section of the Evandro Chagas Institute. The techniques of cell cultures, stock (C6/36), inoculation, extraction, viral load quantification, RTqPCR and statistical analyzes were performed at the Viral Biogenesis Laboratory. Results: According to the results obtained, two cells (HepG2 and Huh7.5) demonstrated a higher level of viral replication at 72 hours post infection (hpi). The PIWI 2 target alter its mRNA expression during VDEN4 infection. The PIWI 4 target expression, was observed an altered expression in the infected cells. Thus, it was found that they are in different poles, while the viral load in the first three days showed high expression. The expression of mRNA was low in relation to the normal rate given by the uninfected cells. Conclusion: In our findings, it was observed that PIWI2 and 4 proteins have an inverse relationship to the viral infection process by VDEN4, when there is an increase in viral replication, these two proteins end up having a significant reduction in their expression. Probably, this reduction of expression is involved with the biogenesis process of apoptosis-regulating microRNAs.